2023
DOI: 10.1186/s12864-023-09529-5
|View full text |Cite
|
Sign up to set email alerts
|

Temporal transcriptomic profiling elucidates sorghum defense mechanisms against sugarcane aphids

Heena Puri,
Sajjan Grover,
Lise Pingault
et al.

Abstract: Background The sugarcane aphid (SCA; Melanaphis sacchari) has emerged as a key pest on sorghum in the United States that feeds from the phloem tissue, drains nutrients, and inflicts physical damage to plants. Previously, it has been shown that SCA reproduction was low and high on sorghum SC265 and SC1345 plants, respectively, compared to RTx430, an elite sorghum male parental line (reference line). In this study, we focused on identifying the defense-related genes that confer resistance to SCA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…This has increased our understanding of the potential mechanisms by which sorghum responds to aphid infestation. Studies have shown that in sorghum, rice and maize plants infested by sorghum aphids, rice stem borers ( Chilo suppressalis ), and corn aphids, the number of upregulated DEGs is higher than the number of downregulated DEG [ 40 42 ], indicating that insect feeding triggers host transcriptome recombination. Similarly, our DEG analysis showed that there were more upregulated DEGs than downregulated DEGs in response to aphid infestation.…”
Section: Discussionmentioning
confidence: 99%
“…This has increased our understanding of the potential mechanisms by which sorghum responds to aphid infestation. Studies have shown that in sorghum, rice and maize plants infested by sorghum aphids, rice stem borers ( Chilo suppressalis ), and corn aphids, the number of upregulated DEGs is higher than the number of downregulated DEG [ 40 42 ], indicating that insect feeding triggers host transcriptome recombination. Similarly, our DEG analysis showed that there were more upregulated DEGs than downregulated DEGs in response to aphid infestation.…”
Section: Discussionmentioning
confidence: 99%
“…(2021) used a different resistant line (TAM48) and was focused on sorghum TFs only. Similarly, the study by Puri et al. (2023) has also used a different resistant line (SC265).…”
Section: Discussionmentioning
confidence: 99%
“…HRGPs are important structural components of plant cell walls and accumulate in response to infection as an apparent defense mechanism [47,48]. Aphid feeding on the sugarcane-aphid-resistant sorghum line resulted in the increased expression of genes related to cell wall formation, including the HRGP gene [49]. TraesCS2D02G460800 had one non-frameshift deletion (nine amino acid residue deletions) in the exon and no SNP/InDel in the promoter.…”
Section: Seven Candidate Genes Have Been Reported To Play Roles In Ap...mentioning
confidence: 99%